The Difference In Transepidermal Water Loss (TEWL) Values Between Sun-exposed and Non-sun-exposed Skin Among Male Medical Students - Prihadi, Ihsany Arafiasetyanto; Ellistasari, Endra Yustin; Kusumawardani, Arie (UI Scholars Hub, 2022)
Background: Transepidermal Water Loss (TEWL) is the amount of water released from the human body into the atmosphere through a diffusion process per unit of time. Changes in TEWL indicate impaired skin barrier function. Exposure to ultraviolet light for an extended period can cause photoaging, characterized by rough and dry skin (xerosis cutis). TEWL will increase significantly in the skin exposed to ultraviolet radiation. This study aims to determine the difference in the TEWL values among male medical students in the sun-exposed and non-sun-exposed skin areas. Methods: An analytical observational cross-sectional study was conducted at the Dermatology and Venereology Department of RSUD Dr. Moewardi Surakarta in January-March 2021. Sampling was carried out through consecutive sampling and 25 samples were obtained. TEWL examination was performed on the dorsal area of the forearm and the medial area of the upper arm using the Tewameter TM300. The mean value of TEWL was analyzed using the non-parametric Wilcoxon signed rank test and Spearman's correlation test. Results: Based on the Wilcoxon signed rank test, there was a significant difference in the value of TEWL (p = 0.000). Spearman correlation analysis shows the coefficient value of r = 0.599, with p = 0.002. Conclusion: There is a significant difference in TEWL values in the sun-exposed skin area compared to the non-sun-exposed skin area, with a moderate positive correlation.